Status of the Golden Eagle Aquila chrysaetos in Veneto (Avocetta, 2017)
The first investigations on the Golden Eagle in Veneto were started in the second half of the 1980s in the provinces of Vicenza (Pedrini & Smaniotto 1993), Belluno and Treviso (Tormen & Cibien 1991). Another research project was then carried out in a smaller territorial area, in the province of Belluno within the Dolomiti Bellunesi National Park, during the AQUILALP project, Intereg III Italy Austria (Tormen et al. 2008). Concerning the province of Verona, where a Golden Eagle’s reproductive population is known, we are unaware of any specific surveys and there are only estimates originating from generic ornithological publications. In all of these cases, investigations have covered only a short time period, and there are therefore no continuous data series over the years, particularly regarding the reproductive success. Following classic methods for investigating raptors, the research took place by identifying the territorial pairs and their nesting sites, and collecting information on the structure of the population, the reproductive success, diet, and factors of disturbance and mortality. Veneto is 18,264 km2 in size, however the mountain range suitable for the Golden Eagle is only 26.3% of the entire regional territory, i.e. about 4800 km2, 3000 km2 of which lies in the province of Belluno (excluding Val Belluna, about 700 km2)